Immunostimulatory Effects of Guanine-Quadruplex Topologies as Scaffolds for CpG Oligodeoxynucleotides - Soumitra Pathak; Nguyen Bui Thao Le; Taiji Oyama; Yusuke Odahara; Atsuya Momotake; Kazunori Ikebukuro; Chiho Kataoka-Hamai; Chiaki Yoshikawa; Kohsaku Kawakami; Yoshihisa Kaizuka; Tomohiko Yamazaki (Biomolecules)
Synthetic cytosine-phosphate-guanine oligodeoxynucleotides (CpG ODNs) are promising candidates for vaccine adjuvants, because they activate immune responses through the Toll-like receptor 9 (TLR9) pathway. However, unmodified CpG ODNs are quickly degraded by serum nucleases, and their negative charge hinders cellular uptake, limiting their clinical application. Our group previously reported that guanine-quadruplex (G4)-forming CpG ODNs exhibit enhanced stability and cellular uptake. G4 structures can form in parallel, anti-parallel, or hybrid topologies, depending on strand orientation, but the effects of these topologies on CpG ODNs have not yet been explored. In this study, we designed three distinct G4 topologies as scaffolds for CpG ODNs. Among the three topology, the parallel G4 CpG ODN demonstrated the highest serum stability and cellular uptake, resulting in the strongest immune response from macrophage cells. Additionally, we investigated the binding affinities of the different G4 topologies to macrophage scavenger receptor-1 and TLR9, both of which are key to immune activation. These findings provide valuable insights into the development of CpG ODN-based vaccine adjuvants.